Iso 9000 from Islamic Perspective - Basir, Siti Arni; Mohd. Sharif, Mohd. Farid; Raja Sulong, Raja Hisyamudin (Jurnal Usuluddin, 2008)
The objective of this paper is to explain the elements of Islamic management which can be integrated with the ISO 9000. This paper considers two themes. Firstly, it focuses on the ISO 9000 requirements. Secondly, it discusses the possible role of the elements of Islamic management in ISO 9000 adoption. It can be concluded that the elements of Islamic management have been neglected in the ISO 9000 adoption. Hence, these factors need to be considered in improving the ISO 9000 adoption.